2020
DOI: 10.1186/s13071-020-04022-4
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional temporal trends (2013–2019) of canine Ehrlichia spp. seroprevalence in the USA

Abstract: Background: In the USA, there are several Ehrlichia spp. of concern including Ehrlichia canis, Ehrlichia ewingii, Ehrlichia chaffeensis, Ehrlichia muris eauclarensis, and "Panola Mountain Ehrlichia". Of these, E. canis is considered the most clinically relevant for domestic dogs, with infection capable of causing acute, subclinical, and chronic stages of disease. Changes in climate, land use, habitats, and wildlife reservoir populations, and increasing contact between both human and dog populations with natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Other factors associated with exposure to CME agents are the dog's habitat, contact with other dogs, and the presence of ticks. Dogs that have contact with other dogs and dogs parasitized by the ticks of R. sanguineus, which are the vector of E. canis, showed a higher likelihood of exposure [3,6,13]. Since R. sanguineus is a three-host tick species, it must complete its life cycle on the ground.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors associated with exposure to CME agents are the dog's habitat, contact with other dogs, and the presence of ticks. Dogs that have contact with other dogs and dogs parasitized by the ticks of R. sanguineus, which are the vector of E. canis, showed a higher likelihood of exposure [3,6,13]. Since R. sanguineus is a three-host tick species, it must complete its life cycle on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is caused by rickettsial bacteria, namely, Ehrlichia canis, transmitted by Rhipicephalus sanguineus (brown dog tick). CME is widely distributed in tropical, Mediterranean, and subtropical climates, including Europe [1,2], the United States [3], Costa Rica [4], Brazil [5], and Asia [6][7][8]. In Thailand, the reported prevalence of E. canis identified using polymerase chain reaction (PCR) in all parts of the country ranges from 7.6% to 38.3% [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Dogs may potentially be a reservoir of certain infectious disease and be a source of infection for ticks ( 77 ). For zoonotic pathogens, dogs may serve as effective sentinels ( 78 , 79 ). For example, seroprevalence of Borrelia burgdorferi in dogs may be a sensitive marker of human risk for Lyme disease as dogs are infected at a higher frequency ( 80 , 81 ).…”
Section: Discussionmentioning
confidence: 99%
“…These tick-borne bacteria are commonly found in the Southern U.S., Brazil, and Mediterranean basin—where L. infantum is endemic among dogs [ 10 , 18 , 90 ]. Dogs are most frequently infected by E. canis , the etiologic agent of canine monocytic ehrlichiosis [ 91 , 92 , 93 ].However, it has been reported that E. ewingii and E. chaffeensis also naturally infect canids [ 13 ]. E. canis is primarily transmitted by Rhipicephalus sanguineus ticks, and E. ewingii and E. chaffeensis are most frequently transmitted by Amblyomma americanum ticks [ 13 , 14 , 15 ].…”
Section: Bacterial Co-infectionsmentioning
confidence: 99%